(untitled) (London Journal of Research In Humanities and Social Sciences, 2024)
Housing is one of the basic needs of life and remains top priority of any person society and economy Housing is one of the basic need of human beings assumes many side significance in terms of degree of economic well being and human development as well as socio-cultural progression and political stability. Indian government implemented several schemes for the mission – “Affordable Housing for All” Increase in population growth coupled with rapidly increasing urbanization and widespread poverty have created a serious shelter problem in India. In the metropolitan cities slums are increased; it leads to the high demand for urban infrastructure and services. As per the technical study conducted by MHUPA (Ministry of Housing and Urban Poverty Alleviation), the urban housing shortage in India is currently estimated at 19 mn. This gap is expected to further widen to an estimated 38 million homes by 2030 largely due to the rising population and increased urbanization. In terms of investment requirements to meet housing shortage, the 33 million units target of the Ninth Five-Year Plan was estimated to require over Rs 1,50,000.00 crores. To partially achieve this fund needed from formal sources such as banks, financial institutions, government-directed insurance companies, and central, state, and local governments. According to the Indian National Sample Survey’s (NSS- 44th round survey) , more than 80 % of housing finance comes from private savings, non-formal sources of credit and sale of assets. Therefore, increasing funding through both the formal sector and informal sector is an essential and integral means to meet the housing needs of low-income households in India. There are certain psychological factors like sense of security ,sense of belonging ,identity,status ,colour and height that affect housing satisfaction among residents .This study attempts to establish the relationship between these variables.